2022
DOI: 10.1021/acs.langmuir.2c01566
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Self-Healing Superhydrophobic Surface for Underwater Drag Reduction

Abstract: The self-healing superhydrophobic surfaces have attracted great interest owing to restoring superhydrophobicity without preparation crafts. However, the self-healing superhydrophobic surface still faces the dilemma of long repairing time. Especially in aqueous environments, superhydrophobic surfaces are highly susceptible to contamination and damage. In the current study, a superhydrophobic surface with ultrafast repairability was developed, which apply for drag reduction in aqueous medium. The prepared superh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…36 Sun et al prepared a superhydrophobic surface with a repairable irregular void structure and found that the porous superhydrophobic surface could enhance the stability of the underwater gas−liquid interface and significantly reduce the frictional resistance. 37 39 However, there are obvious drawbacks to generating air cavities for underwater drag reduction using the above method: (1) The micro/nanostructure of SHSs is highly susceptible to damage and poor adhesion between the coating and the substrate, making it difficult for the surface to trap air layers, producing wall slippage and preventing drag reduction under extreme environmental conditions. (2) The Leidenfrost effect generates air cavities that require the spheres to be heated above the Leidenfrost temperature of liquid, but the repeated impingement of spheres into the water causes the surface temperature to drop, causing the vapor layer on the surface to gradually collapse, which in turn affects the hydrodynamic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Sun et al prepared a superhydrophobic surface with a repairable irregular void structure and found that the porous superhydrophobic surface could enhance the stability of the underwater gas−liquid interface and significantly reduce the frictional resistance. 37 39 However, there are obvious drawbacks to generating air cavities for underwater drag reduction using the above method: (1) The micro/nanostructure of SHSs is highly susceptible to damage and poor adhesion between the coating and the substrate, making it difficult for the surface to trap air layers, producing wall slippage and preventing drag reduction under extreme environmental conditions. (2) The Leidenfrost effect generates air cavities that require the spheres to be heated above the Leidenfrost temperature of liquid, but the repeated impingement of spheres into the water causes the surface temperature to drop, causing the vapor layer on the surface to gradually collapse, which in turn affects the hydrodynamic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zhang et al were inspired by the fine hairs and cilia of living organisms to prepare a hair-like superhydrophobic surface by electrostatic value linting and subsequent surface modification, which has excellent mechanical stability and enables an effective drag reduction effect . Sun et al prepared a superhydrophobic surface with a repairable irregular void structure and found that the porous superhydrophobic surface could enhance the stability of the underwater gas–liquid interface and significantly reduce the frictional resistance . Zhu et al prepared slippery liquid-infused porous surfaces (SLIPSs) by injecting lubricating fluid on the surface of porous microstructured spheres .…”
Section: Introductionmentioning
confidence: 99%
“…One way to reach this goal is to impose slip velocity on the fluid at a close adjacency to the solid wall by virtue of altering surface wettability. Liquid-infused surfaces (LISs) and superhydrophobic surfaces are two types of non-wetting surfaces that could be utilized for this purpose. …”
Section: Introductionmentioning
confidence: 99%
“…Reduction of fluid resistance is of significance to increasingly emerging energy and environmental issues. Turbulence is the major source of fluid resistance in many cases and has attracted extensive attention. Hence, research into drag reduction has focused on methods to depress turbulence near walls. Biomimetic riblet surfaces, such as blade, wavy, sinusoidal, and herringbone riblet (Blade, Wavy, Sinusoidal, and Herringbone, respectively) surfaces, inspired by sharks and birds have achieved significant reductions in turbulent drag reduction. Blade surfaces have been proven to provide obvious drag reduction, and they have shown promise for many potential applications in the pipeline, aircraft, energy, and transportation industries. , …”
Section: Introductionmentioning
confidence: 99%